Upaya Meningkatkan Motorik Halus Melalui Kegiatan Mozaik dengan Menggunakan Bahan Alam Pada Anak Usia 4-5 Tahun di TK Nusantara Islamic School Bekasi - Ashanti, Rina; Yenita, Roza; Hamidah, Agustin (CV. ITTC INDONESIA, 2024)
Based on initial observations at Nusantara Islamic School Kindergarten, it was found that most children aged 4 to 5 years still have difficulties in developing their fine motor skills. This can be seen from the lack of hand-eye coordination, difficulty in holding and using stationery correctly, and lack of precision in carrying out activities that require fine motor skills.The research method used by researchers in this study is the Action Research method or Classroom Action Research (PTK). The percentage results obtained at the pre-cycle stage were 10% and cycle II 80%. Based on the results of the table, it can be described that fine motor skills through mosaic activities in children aged 4 to 5 years at Nusantara Islamik School Bekasi Kindergarten have increased.